Performing a physiologically relevant test for cladribine tablets - P. A. Losenkova; D. D. Gvozdev; A. V. Suvorova; Yu. V. Medvedev; V. S. Shcherbakova; Yu. G. Kazaishvili; K. Ya. Zaslavskaya; A. M. Poluyanov; I. E. Shohin (Разработка и регистрация лекарственных средств)
Introduction. The introduction of devices – analogues of GIS (hereinafter–- Gastro-intestinal simulator) is one of the current ways to develop in-vitro assessment of the quality of solid dosage forms. Testing on a physiologically relevant test device (hereinafter referred to as PRT) makes it possible to predict pharmacokinetic profiles due to more relevant conditions, including the use of biorelevant dissolution media, physiological volumes of the gastrointestinal tract, as well as transit between them.Aim. Conduct a study of cladribine tablets on a physiologically relevant tester in order to predict the behavior of the drug in the human gastrointestinal tract.Materials and methods. The objects of the study are "Mavenclad®, tablets, 10 mg" (series 2200754, expiration date until 04.2025, NERPHARMA, S.r.L., Italy) and "Cladribine, tablets, 10 mg" of domestic production with valid expiration date. During the study, the reagents necessary for the preparation of biorelevant dissolution media and quantitative determination by HPLC. Physiologically relevant test were carried out using an apparatus of our own production, consisting of a DT-6 dissolution tester (ERWEKA GmbH, Germany), a water bath equipped with a Thermomix WB-4 heating element (B. Braun, Germany), and peristaltic pumps (Kamoer, China). The quantitative content of released cladribine was assessed using a highly efficient liquid chromatograph "Khromatek-Kristall HPLC 2014" (ZAO SKB "Khromatek", Russia) using a validated method at a wavelength of 252 nm, analysis time – 7 min, column – Grace HPLC Column Platinum C18-EPS, 250 × 4.6 mm, 5 mm (Grace, USA), temperature – 35 °C, elution mode – isocratic (A : B 80 : 20), mobile phase A – 0.1 % H3PO4 solution, phase B – acetonitrile.Results and discussion. Profiles were obtained to assess the dynamics and degree of release of the studied drugs in various parts of the human gastrointestinal tract. Despite the expected degradation of cladribine in an acidic environment (pH1.2), under physiologically relevant conditions, the drug reached the third section (small intestine model) without degradation. Complete release of cladribine from the test and reference dosage forms was observed. Also, in the future, based on the data obtained, it is possible to predict pharmacokinetic profiles using physiologically based pharmacokinetic modeling approaches.Conclusion. A PSF study was conducted for the drugs "Mavenclad®, tablets, 10 mg" and "Cladribine, tablets, 10 mg". Quantitative determination was carried out by HPLC-UV method. The test results showed complete release of both drugs and reaching the intestinal tract, indicating the absence of degradation of cladribine in the region simulating the stomach.